Politik Adaptasi Perubahan Iklim dalam Pendekatan Multilevel Governance di Kota Semarang - Aisya, Naila Sukma (Jurnal Hubungan Internasional, 2019)
Semarang City, one of the biggest cities in Indonesia, experienced tidal floods due to climate change, which require systemic responses. The absence of a legal foundation to overcome the effects of climate change has prompted Semarang City Government to formulate a climate change adaptation policy. Mercy Corps – Asian Cities Climate Change Resilience Network (ACCCRN) opens climate change adaptation cooperation by assigning Semarang City as one of the core cities of ACCCRN. This study aims to analyze the climate change adaptation policy-making process in cooperation between Semarang City Government and ACCCRN using vertical and horizontal interactions of multilevel governance approach. This study also uses the indicators of urban climate change adaptation process to identify the elements of climate change adaptation policy in Semarang City. The vertical interactions show that the climate change adaptation negotiations at the international and national levels urge an adaptation policy-making in Semarang City. Meanwhile, in horizontal interactions, Semarang City Government in cooperation with Mercy Corps – ACCCRN tries to formulate an inclusive climate change adaptation policy through Shared Learning Dialogues (SLDs) mechanism. As a result, Semarang City Government produces climate change adaptation policy, namely Semarang Resilience Strategy.